2021
DOI: 10.4111/icu.20210060
|View full text |Cite
|
Sign up to set email alerts
|

Effect of training and individual operator's expertise on prostate cancer detection through prostate biopsy: Implications for the current quantitative training evaluation system

Abstract: Purpose This study was conducted to evaluate the relevance of training and experience to gaining expertise in prostate biopsy based on an assessment of outcomes from the performance of urology residents. Materials and Methods We retrospectively reviewed the medical records of 10,299 patients who underwent prostate biopsy by 50 operators under a unified urology residency program. The number of prostate biopsies performed by an operator for each patient was used as an ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…This result could be explained by the fact that biopsies are performed most frequently at this level of training in our clinic. As Lee and Mager et al have already shown, there is a learning curve of 40-50 targeted biopsies, after which the detection rate is sufficient and sometimes even higher than the expert standard of the institution (9,17). This is likely a practice effect, which makes those who perform many biopsies at the time of the survey perform better.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This result could be explained by the fact that biopsies are performed most frequently at this level of training in our clinic. As Lee and Mager et al have already shown, there is a learning curve of 40-50 targeted biopsies, after which the detection rate is sufficient and sometimes even higher than the expert standard of the institution (9,17). This is likely a practice effect, which makes those who perform many biopsies at the time of the survey perform better.…”
Section: Discussionmentioning
confidence: 98%
“…Even in radical prostatectomy, a detailed understanding of the tumor localization in mpMRI as well as a high quality prostate biopsy is essential for safe resection margins and nerve sparing ( 10 , 16 ). However, achieving a comprehensive understanding of mpMRI is still a major challenge for many urologists worldwide ( 4 , 5 ) and requires a high level of experience ( 4 , 7 , 9 , 17 ). After implementation of mpMRI and targeted prostate biopsies into the EAU-guidelines as the gold standard diagnostic for prostate cancer ( 3 ) the demand for targeted prostate biopsies has increased drastically.…”
Section: Discussionmentioning
confidence: 99%